Critical pedagogies and the theatre laboratory. Issue 2 (3rd April 2017) - Heron, Jonathan; Johnson, Nicholas
ABSTRACT: This dialogue contributes reflections on the 'theatre laboratory' to the scholarly debate surrounding methodologies of drama education and applied performance. The co-authors suggest that the experimental and ensemble-led approach of the Samuel Beckett Laboratory, founded at Trinity College Dublin in 2013 as a space for research into Beckett in performance, may offer one response to a question that Kathleen Gallagher proposes in the twentieth Anniversary issue of RiDE (20.3), concerning 'how drama educators might incorporate such practices of hope into their pedagogy' [2015. "Beckoning Hope and Care." RIDE: The Journal of Applied Theatre and Drama Education 20 (3): 423]. This work suggests that the hopeful practice of laboratory exploration de-hierarchises a scholarly endeavour and recasts the student as co-creator of knowledge, rather than consumer of cultural capital. The values and practices of such a laboratory may open one avenue of participatory pedagogy that scaffolds risk and re-values failure. In the dialogue that follows, we draw on Gallagher's 'practices of hope' to develop our own interests in the subjunctivity of performance pedagogies in Beckettian contexts [cf. Heron, J., N. Johnson, B. Dinçel, G. Quinn, S. J. Scaife, and Á. Tyrrell, 2014. "The Samuel Beckett Laboratory 2013." Journal of Beckett Studies 23 (1): 73–94].